Shopping to Release Stress? Understanding The Role of Coping Stress and Gender on Online Shopping Behavior in College Students During the COVID-19 Pandemic - Wahyu Rahardjo; Kenes Pranandari; Dona Eka Putri; Nurul Qomariyah; Quroyzhin Kartika Rini; Inge Andriani (Jurnal Psikologi Teori dan Terapan, 2023)
In the context of a pandemic, many people are still trying to fulfill their various needs by buying them online. However, the phenomenon of online shopping behavior in a pandemic is no longer a behavior to meet primary needs but is also thought to be carried out as a form of coping strategy to reduce perceived stress. The purpose of this study is to empirically measure to what extent coping stress can affect online shopping behavior by college students during a pandemic. This study uses the online shopping behavior scale owned by Haidery et al. (2020) and coping stress scale from Martinez-Lopez et al. (2016). This study involved 453 college students from grade 1 to grade 4 who lives in Jakarta Greater area. The main data analysis technique in this research is Anacova. The results showed that by considering gender, coping with stress significantly affected online shopping behavior in college students during the pandemic. Another finding in this research also reveals that female students tend to display online shopping behavior and use shopping as coping stress compared to male students.